LOGICAL AND COMPETENCY APPROACH IN LEARNING SPORTS DISCIPLINES - Yury D. Ovchinnikov (Высшее образование в России)
The article demonstrates the propriety of applying the logical and competency approach instudying sports disciplines by example of the course «Biomechanics of the locomotor activity». The interrelation between cultural and professional competences and the basic information through a modular system, step0by0step algorithm of skills is shown.